A história da supervisão na formação do analista: de Breuer a Lacan - Valli, Cristiane Maretti Marangoni (2015)
The current thesis aims at conceiving the multiple senses that the history of the supervision encompasses in the professional development of the analyst, from the Breuer period to the Lacanian era. In order to accomplish such task, the psychoanalytical writings that refer to supervision were taken as the object of study and were read and comprehended in an analytical way through the use of the psychoanalytical method. As a result of this method, this proposal revealed that situations of supervision can be identified even before Freud s psychoanalytical knowledge had been unveiled. The analysis also highlighted that, during supervision, the desire to become an analyst connected transferentially to an Other (many times idealised) that was seen as the knowledge holder, which can engender an actual analyst. The interpretation of the psychoanalytical texts also showed in depth how the supervision practice was originated, how and the reason why it was developed and became the pillar of the professional development. The systematization and institutionalization of the analyst professional development brought important impasses in its core that resulted in ruptures inside the psychoanalytical movement. Such ruptures led to the building of another professional development model in order to solve such impasses; however, it fell back into the same mistake they wanted to avoid, leading to more dissensions